1995
DOI: 10.1093/clinids/21.6.1417
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Associated with Nosocomial Bacteremia Due to Methicillin-Resistant Staphylococcus aureus

Abstract: We prospectively studied all cases of Staphylococcus aureus bacteremia that occurred during an extensive outbreak of methicillin-resistant S. aureus (MRSA) in our hospital over a 4-year period (January 1990 through September 1993). We report the results of a comparative analysis of the clinical characteristics and mortality rates among patients with nosocomial bacteremia caused by MRSA (84 cases) or methicillin-susceptible S. aureus (MSSA; 100 cases). The patients with MRSA bacteremia were older than those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
149
2
10

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(172 citation statements)
references
References 39 publications
11
149
2
10
Order By: Relevance
“…and meningitis) are improved by early therapy with active agents against the organisms which are subsequently identified by appropriate culture. Subsequently testing and provision of inadequate therapy is closely correlated with adverse patient outcomes, including increased rates of hospital mortality [39][40][41][42]. Solomkin et al (2004) affirmed that hospitals with more than 20% of MRSA should use vancomycin in empiric treatment [43].…”
Section: Appropriate Use Criteriamentioning
confidence: 99%
“…and meningitis) are improved by early therapy with active agents against the organisms which are subsequently identified by appropriate culture. Subsequently testing and provision of inadequate therapy is closely correlated with adverse patient outcomes, including increased rates of hospital mortality [39][40][41][42]. Solomkin et al (2004) affirmed that hospitals with more than 20% of MRSA should use vancomycin in empiric treatment [43].…”
Section: Appropriate Use Criteriamentioning
confidence: 99%
“…Staphylococcus aureus is the etiologic agent for a remarkable variety of skin, soft tissue, respiratory, bone, joint, and cardiovascular disorders [7][8][9][10][11]. While many factors are thought to contribute to the ability of S. aureus to cause a range of clinical disease, recent work has indicated that the bacterium can bypass a competent immune response with some degree of efficiency.…”
mentioning
confidence: 99%
“…22 In this surveillance project, slightly more than one-third of the patients had an MRSA infection, including 13% who were bacteremic. Several studies have documented that MRSA infections are associated with greater mortality rate and length of hospital stay, [28][29][30][31][32] and that after adjustment for comorbidities methicillin resistance is a significant independent risk factor for death. 29,30 MRSA is typically resistant to multiple classes of antibiotics.…”
Section: Discussionmentioning
confidence: 99%